The Advent of Capitalism and Malay Dilemma in Money Economy: The Foundation of Business Corporation and Cooperative Societies in Colonial Malaya (Paramita: Historical Studies Journal, 2021)
Abstract: This article discusses the Malay dilemma in facing the expansion of money economy in the Malay society in early 20th century Malaya. Historically, the advent of capitalism during this period instigated the growing importance of money economy. However, in the rural economy, the Malay commoners known as ‘rakyat’ were not widely exposed to money economy. The prevalence of money economy in the Malay society was limited to the Malay upper class of royal kinsmen and nobles because of their dominance over the surplus, notably found in the form of taxation imposed on the rakyat who were mostly peasants. This situation began to change in the beginning of the 20th century when credit facilities for agricultural activities became available for the Malay commoners that eventually paved the way for the rakyat to gradually venture into small businesses and be exposed to money economy. In order to address the problem related to indebtedness, there were initiatives to establish cooperative societies for rural credits. However, these initiatives were always overshadowed by the imposition of interests on the loans. This is because such interests were perceived as riba’ or usury, which were regarded as haram or impermissible in Islam. Nevertheless, based on historical circumstances, it can be argued that the establishment of cooperative societies was regarded as the more viable means than business ventures in incorporating the Malay peasant community into money economy. Abstrak: Artikel ini membahas dilema Melayu dalam menghadapi ekspansi ekonomi uang dalam masyarakat Melayu di Malaya awal abad ke-20. Secara historis, munculnya kapitalisme selama periode ini mendorong semakin pentingnya ekonomi uang. Namun, dalam perekonomian pedesaan, rakyat jelata Melayu yang dikenal sebagai 'rakyat' tidak banyak terekspos pada ekonomi uang. Prevalensi ekonomi uang dalam masyarakat Melayu terbatas pada kelas atas Melayu dari kerabat dan bangsawan kerajaan karena dominasi mereka atas surplus, terutama ditemukan dalam bentuk pajak yang dikenakan pada rakyat yang sebagian besar adalah petani. Situasi ini mulai berubah pada awal abad ke-20 ketika fasilitas kredit untuk kegiatan pertanian tersedia bagi rakyat jelata Melayu yang pada akhirnya membuka jalan bagi rakyat untuk secara bertahap terjun ke bisnis kecil dan terpapar pada ekonomi uang. Untuk mengatasi permasalahan yang berkaitan dengan hutang tersebut, maka terdapat inisiatif untuk membentuk perkumpulan koperasi untuk kredit pedesaan. Namun, inisiatif ini selalu dibayangi oleh pengenaan bunga atas pinjaman. Sebab, kepentingan tersebut dianggap sebagai riba yang dianggap haram atau tidak diperbolehkan dalam Islam. Namun demikian, berdasarkan keadaan historis, dapat dikatakan bahwa pendirian koperasi dianggap sebagai cara yang lebih layak daripada usaha bisnis dalam memasukkan masyarakat petani Melayu ke dalam ekonomi uang.